STUDY ON THE CORRELATION OF PHYSIOLOGICAL PARAMETERS AT MINI-FOOTBALL PLAYERS - STEGARIU V.I; TROFIN F.P; ABALAȘEI B.A (Editura Universitatii Transilvania din Brasov, 2020)
We tested a group of 12 athletes, mini-football players, from Romania who regularly perform in the first league. The athletes were subjected to an evaluation that aimed to determine: height, body mass, movement speed, agility, explosive power, lactic anaerobic capacity and maximum oxygen consumption. The analysis of the results led to the identification of significant correlations between the speed of movement and agility (r2 =0.71), leg's explosive power and reaction time of the nondominant leg (r2 =-0.61), lactic anaerobic capacity and body mass (r2 =0.60).This study highlights the links established between the physical parameters of the mini-football players from Romania.